Coagulation mixing studies: Utility, algorithmic strategies and limitations for lupus anticoagulant testing or follow up of abnormal coagulation tests - Favaloro, Emmanuel J. (American journal of hematology, 2020)
Coagulation testing underpins the investigation of hemostasis and/or monitoring of anticoagulation therapy for prevention and/or treatment of thrombosis related pathology. Assessment of coagulation results requires comparison against a normal reference range or interval (NRR/NRI). Results flagged as “abnormal” (ie, above the NRR/NRI for patients not on anticoagulant therapy), typically require further evaluation. eg, follow up or reflexive testing is used to identify the reason for prolongation, especially when supported by clinical context (eg, bleeding). Mixing tests may have utility to help identify the pathway of follow‐up testing (ie, towards investigation of factor deficiencies, or else inhibitors), and are also useful for investigation of lupus anticoagulants (LA). In general, mixing tests that “correct” tend to suggest the presence of factor deficiencies, where as those that do not correct suggest the presence of “inhibitors”. Various approaches can be used to identify correction/non‐correction, and all have strengths and limitations. Furthermore, eventual identification of causal factor deficiencies or even “inhibitors” may (eg, factor VIII or IX deficiencies or inhibitors) or may not (eg, factor XII deficiency) be clinically important. Ultimately, mixing studies performed in view of appropriate clinical scenarios (eg, bleeding patient) and for LA investigations in symptomatic patients will have best utility.